NILAI-NILAI PENDIDIKAN ISLAM DALAM SHALAWAT JAWA DI DESA BANDAR KABUPATEN PACITAN - Sawitri Sawitri; Moh Masduki (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of this study was to find: 1) how to carry out the "Javanese prayer" cultural title in Dukuh Krajan, Bandar Pacitan Village. 2) To find out what is unique about "Javanese prayer" from other prayers, 3) To know the values of Islamic education in the "shalawat" culture Java” in Dukuh Krajan, Bandar Pacitan Village. This research uses qualitative research. The data collection technique used is participant observation. In-depth interviews (in-depth interviews), and documentation (document review), while the data analysis method used is Miles and Huberman's model, including the stages of data collection, data reduction, data presentation, and drawing conclusions. The procedures for performing the Javanese prayer are: 1) preparing the equipment used in the prayer ceremony, such as drums, large flying, small flying, ketipung, and places. 2) the opening from the leadership of the Shalawat Grub. 3), start singing the strains of the Shalawat song, a specialty of the Javanese Shalawat lies only in language, tone, and curvature. The value of moral education in the Javanese Shalawat culture includes: helping out in trouble, such as working together and respecting each other.